Beautiful disaster eaudiobook - McGuire, Jamie (Beautiful Disaster, 2014)
The new Abby Abernathy is a good girl. She doesn't drink or swear, and she has the appropriate number of cardigans in her wardrobe. Abby believes she has enough distance from the darkness of her past, but when she arrives at college with her best friend, her path to a new beginning is quickly challenged by Eastern University's Walking One-Night Stand. Travis Maddox, lean, cut, and covered in tattoos, is exactly what Abby wants—and needs—to avoid. He spends his nights winning money in a floating fight ring, and his days as the ultimate college campus charmer. Intrigued by Abby's resistance to his appeal, Travis tricks her into his daily life with a simple bet. If he loses, he must remain abstinent for a month. If Abby loses, she must live in Travis's apartment for the same amount of time. Either way, Travis has no idea that he has met his match.